Design and performance study of MAC protocols in muti-hop wireless sensor networks - Liu, Ming. (2010)
A Wireless Sensor Network (WSN) consists of many distributed sensor nodes to monitor physical or environmental conditions within a certain range. The development was initially motivated by military application purpose and it becomes more and more popular nowadays. Medium Access Control (MAC) protocols play a crucial role in WSN communication. In recent years, as more and more researchers join in the WSN study and development, many MAC protocols have been proposed and some of them managed to achieve energy-efficiency, low latency etc.. However, there is still much space to further improve. This project aims to further improve the performance of Adaptive Scheduling MAC (AS-MAC) protocol which is developed by Zhao Yizhi and NguyenThuy Ngoc based DW-MAC last year. The improvement is achieved by introducing an algorithm which can automatically adjust the TSLEEP duration according to different Event Intervals.